2007
DOI: 10.1254/jphs.sc0070184
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation With the Combination of Simvastatin and Calcium Sulfate in Critical-Sized Rat Calvarial Defect

Abstract: Abstract. Simvastatin, a cholesterol synthesis inhibitor, enhances BMP2 expression in osteoblasts. The purpose of the present study was to examine whether simvastatin stimulates bone regeneration when combined with calcium sulfate as a carrier. Critical-sized bone defects in rat calvaria were treated with calcium sulfate or with combination of 1 mg simvastatin and calcium sulfate. In the combination group, although the least amount of bone formation with intense soft tissue inflammation was observed at 2 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 11 publications
6
99
1
7
Order By: Relevance
“…4 In the present study, the use of high local doses of simvastatin caused an intense inflammatory reaction, accompanied by tissue necrosis and scabbing. Soft tissue inflammation was also reported by Thylin et al, 6 who used 2.2 mg of the drug in methylcellulose gel in rat calvaria; by Nyan et al, 9 who used 1 mg of the drug in calcium sulfate in rat calvaria; and by Stein et al, 7 who used doses of 0.5, 1.0, 1.5, and 2.2 mg of the drug in rat mandible. In the study conducted by Stein et al, 7 the 0.5-mg dose presented the best cost-benefit ratio, promoting significant bone formation and reduced inflammation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…4 In the present study, the use of high local doses of simvastatin caused an intense inflammatory reaction, accompanied by tissue necrosis and scabbing. Soft tissue inflammation was also reported by Thylin et al, 6 who used 2.2 mg of the drug in methylcellulose gel in rat calvaria; by Nyan et al, 9 who used 1 mg of the drug in calcium sulfate in rat calvaria; and by Stein et al, 7 who used doses of 0.5, 1.0, 1.5, and 2.2 mg of the drug in rat mandible. In the study conducted by Stein et al, 7 the 0.5-mg dose presented the best cost-benefit ratio, promoting significant bone formation and reduced inflammation.…”
Section: Discussionmentioning
confidence: 63%
“…5,9,10 Others, however, have found no beneficial effects. 9,19,20 The ideal doses and carriers have yet to be determined, and the issue remains controversial. Low doses have no impact on bone repair, whereas high doses can stimulate inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have demonstrated that bilateral treatment of the posterolateral spine with rhBMP-2 resulted in complete spinal fusion in 100% of patients receiving the treatment. 9,73 The action of BMPs in vivo can even be enhanced by coadministration of NELL-1, 2 COX-2 inhibitors, 65 treatment with simvastatin, 86 or a combination of simvastatin and a-TCP. 85 Last, it is important to clarify that in Europe, rhBMP-2 is commercially available for the treatment of acute open tibial fractures (InductOS implant kit, Medtronic Sofamor Danek and Wyeth Pharmaceuticals) as a lyophilized powder, dissolved in sterile water, and applied to an absorbable collagen matrix made of Type 1 bovine collagen.…”
Section: Recombinant Protein-based Strategiesmentioning
confidence: 99%
“…La materia prima de la que se hace es relativamente barata y abundante, se puede combinar con otros materiales como autoinjertos, aloinjertos, fosfatos de calcio, y vidrios bioactivos, para aumentar sus propiedades de unión, el volumen y la eficacia de los injertos óseos. También ha servido como un material de vehículo excelente para los factores de crecimiento y múltiples drogas, a pesar de estas ventajas, el material no ha gozado de la popularidad de muchos otros materiales de regeneración, aunque recientemente ha recibido una atención renovada con propiedades hemostáticas, angiogénicas y de barrera o membrana para la preservación de rebordes alveolares postexodoncias (1)(2)(3)(4)(5)(6)(7)(8) . …”
Section: Introductionunclassified